2000
DOI: 10.1292/jvms.62.815
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Variation of Mandible Size and Shape in the Japanese Wild Pig (Sus scrofa leucomystax)

Abstract: ABSTRACT. The mandibles of the Japanese wild pigs (Sus scrofa leucomystax) from various geographical locations, which have been stored in the University of Tokyo and National Science Museum, Tokyo were examined. The mandibles from northern localities were larger in size than those from southern localities. The Oita population was significantly smaller than the Honshu populations. The Mie population was smaller than the Hyogo population in length from the angle of the mandible. In the multivariate analysis, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Endo et al . () suggested that geographic variation in the mandibles of Sus scrofa (Cetartiodactyla: Suidae; Linnaeus, 1758) is affected by environmental variables (e.g. temperature and altitude).…”
Section: Introductionmentioning
confidence: 99%
“…Endo et al . () suggested that geographic variation in the mandibles of Sus scrofa (Cetartiodactyla: Suidae; Linnaeus, 1758) is affected by environmental variables (e.g. temperature and altitude).…”
Section: Introductionmentioning
confidence: 99%
“…Not all insular elephants are small: Smith et al. (2003) list a higher mass for Elephas maximus on Sri Lanka than for continental ones; however, dwarfism seems to be the rule for proboscideans and artiodactyls (Sondaar, 1977; Lister, 1989; Endo et al. , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…riukiuanus ), on the Ryukyu archipelago (the islands of Amami‐Oshima, Kakeroma, Tokuno‐shima, Okinawa, Ishigaki and Iriomote). The Ryukyu wild boar is smaller than the Japanese wild boar (Endo et al . 1998, 2000), and there are documented genetic differences between the two subspecies (Watanabe et al .…”
Section: Introductionmentioning
confidence: 99%
“…There are two wild boar subspecies in Japan: Japanese wild boars (S. s. leucomystax), on the three main Japanese islands of Honshu, Shikoku and Kyushu; and Ryukyu wild boars (S. s. riukiuanus), on the Ryukyu archipelago (the islands of Amami-Oshima, Kakeroma, Tokuno-shima, Okinawa, Ishigaki and Iriomote). The Ryukyu wild boar is smaller than the Japanese wild boar (Endo et al 1998(Endo et al , 2000, and there are documented genetic differences between the two subspecies (Watanabe et al 1985; Kurosawa & Tanaka 1988;Kurosawa et al 1984;Watanabe et al 1999). For many years, there has been controversy regarding the origin and ancestry of the Ryukyu wild boar.…”
Section: Introductionmentioning
confidence: 99%